CD-Aware Precoder Based on the Sparse ZC Sequence for OFDM-NOMA-PON - Wang, Geyang; Chen, Lian-Kuan (IEEE photonics technology letters, 2026)
Emerging reconfigurable point-to-multipoint fronthaul architecture requires a dynamic connection between optical network units and multiple optical line terminals and joint optimization between the optical and mobile wireless ends, resulting in rapidly time-varying channel state information (CSI). Traditional schemes such as adaptive bit and power loading techniques relying on periodic CSI updating thus become prohibitively complex. Channel-independent precoding schemes, designed to circumvent CSI feedback, offer simpler alternatives; however, their effectiveness deteriorates significantly under chromatic dispersion (CD)-induced spectral nulls in intensity-modulation direct-detection passive optical networks (PONs) systems. To address these limitations, we propose a low-complexity, CD-aware precoding technique based on sparse Zadoff-Chu (SZC) sequences for orthogonal frequency division multiplexing (OFDM)-based non-orthogonal multiple access (NOMA) PON. The SZC scheme not only achieves a flatter SNR profile compared to conventional precodings but also eliminates complex subcarrier-level optimizations. Experimental demonstrations confirm data rates of ~50 and ~70 Gbit/s over 20-km transmission, achieving receiver sensitivity improvements of ~4 dB and ~2 dB over the conventional OFDM-PON and the optimized alternative schemes in the 70-Gbit/s system, respectively.